2011
DOI: 10.1021/es201489n
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Nitrous Oxide Production during Biological Nitrogen Removal via Nitrification and Denitrification: Extensions to the General ASM Models

Abstract: Nitrous oxide (N(2)O) can be formed during biological nitrogen (N) removal processes. In this work, a mathematical model is developed that describes N(2)O production and consumption during activated sludge nitrification and denitrification. The well-known ASM process models are extended to capture N(2)O dynamics during both nitrification and denitrification in biological N removal. Six additional processes and three additional reactants, all involved in known biochemical reactions, have been added. The validit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
164
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 173 publications
(174 citation statements)
references
References 26 publications
6
164
0
1
Order By: Relevance
“…Nitrate reduction consists 46 of four consecutive reduction steps, with nitrite (NO2 -), nitric oxide (NO) and nitrous oxide 47 (N2O) as three obligatory intermediates (Zumft 1997). Each reduction step is catalysed by 48 one or more specific enzymes, including nitrate reductase (Nar), nitrite reductase (Nir), NO 49 is increasingly recognised that N2O accumulation should also be modelled, especially due to 75 its detrimental influence on the atmosphere (Ni et al 2011). It has been proposed to achieve 76 this goal through modelling denitrification as a four-step process, using NO3 -, NO2 -, NO, and as a separate and independent oxidation-reduction reaction (Figure 1-a), and reaction-specific 89 kinetics are applied.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrate reduction consists 46 of four consecutive reduction steps, with nitrite (NO2 -), nitric oxide (NO) and nitrous oxide 47 (N2O) as three obligatory intermediates (Zumft 1997). Each reduction step is catalysed by 48 one or more specific enzymes, including nitrate reductase (Nar), nitrite reductase (Nir), NO 49 is increasingly recognised that N2O accumulation should also be modelled, especially due to 75 its detrimental influence on the atmosphere (Ni et al 2011). It has been proposed to achieve 76 this goal through modelling denitrification as a four-step process, using NO3 -, NO2 -, NO, and as a separate and independent oxidation-reduction reaction (Figure 1-a), and reaction-specific 89 kinetics are applied.…”
mentioning
confidence: 99%
“…It has been proposed to achieve 76 this goal through modelling denitrification as a four-step process, using NO3 -, NO2 -, NO, and as a separate and independent oxidation-reduction reaction (Figure 1-a), and reaction-specific 89 kinetics are applied. Many of the multiple step denitrification models have adopted such 90 structure (e.g., Ni et al (2011), Schulthess and Gujer (1996). …”
mentioning
confidence: 99%
“…The NH 4 + concentration in Run 2 hardly increased during the first 2 h of Phase II, meaning that AOB oxidized NH 4 + to NO 2 -soon after the DO concentration became 0 mg/L. Ni et al (2011) have reported that NO 2 -can be used as an electron acceptor instead of O 2 when DO concentration is low. The first 2 h compared with the rest of the time in Phase II, accumulation of NH 4 + was completely quenched.…”
Section: Discussion N 2 O Production Under Power Saving Conditionsmentioning
confidence: 99%
“…Parameter identifiability was revealed by analyzing the 95% confidence intervals of the individual parameter estimate and the joint confidence regions for different parameter combinations [35]. conditions.…”
Section: Complexity and Identifiability Of The Proposed Modelmentioning
confidence: 99%